Vendredi soir Based on a Novel by Emmanuèle Bernheim - Denis, Claire; Godard, Agnès; Lemercier, Valérie; Lindon, Vincent; Saint-Père, Hélène de (Tartan Video, 2004)
When Laura leaves her apartment to have dinner with friends, she unwittingly drives into one of the biggest traffic jams that Paris has ever experienced. Captive to the night, and with nothing else to do, she listens to the radio and lets her imagination run wild. As pedestrians are caught in the rain, Laura sees a stranger and impulsively decides to take a chance. And so begins a night of unplanned and unrestrained sensuality ... [Cover]